Sharing executive power : roles and relationships at the top - Alvarez, José Luis (Cambridge University Press, 2005)
In many companies, two or three executives jointly hold the responsibilities at the top-from the charismatic CEO who relies on the operational expertise of a COO, to co-CEOs who trust in inter-personal bonds to achieve professional results. Their collaboration is essential if they are to address the dilemmas of the top job and the demands of today's corporate governance. Sharing Executive Power examines the behaviour of such duos, trios and small teams, what roles their members play and how their professional and inter-personal relationships bind their work together. It answers some critical questions regarding when and how such power sharing units form and break up, how they perform and why they endure. Understanding their dynamics helps improve the design and composition of corporate power structures. The book is essential reading for academics, graduates, MBAs, and executives interested in enhancing teamwork and cooperation at the top.